Pembangunan Ekonomi dan Ekonomi Pembangunan: Telaah Istilah dan Orientasi dalam Konteks Studi Pembangunan - Mit Witjaksono (Jurnal Ekonomi dan Studi Pembangunan, 2009)
This article seeks to clarify the meaning, usage, and scope of the terms: economic development and development economics, within the context of development studies. Although there is no generally accepted in a single definition, upon this critical review it is hoped that we will employ those terms and its variants appropriately within the context of development studies.Keywords: economic development, development economics, local economic development, community economic development, economic developer, economic and development studies